Fluid-structure interaction study of bio-magnetic fluid in a wavy bifurcated channel with elastic walls - Shahzad, Hasan; Wang, Xinhua; Raizah, Zehba; Riaz, Arshad; Majeed, Afraz Hussain; Anwar, Muhammad Adnan; Eldin, Sayed M. (Frontiers in Physics, 2022)
As a result of its wide range of applications, FSI has grabbed the attention of researchers and scientists. In this study we consider an incompressible, laminar fluid flowing through the bifurcated channel. The wavy walls of the channel are considered elastic. Moreover, a magnetic field is applied towards the axial direction of the flow. Using a two-way fluid-structure interaction, an Arbitrary Lagrangian-Eulerian (ALE) formulation is used for coupling the problem. The problem is discretized using P_2 and P_1 finite element methods to approximate the displacement, pressure, and velocity. The linearized system of equations is solved using Newton’s iterative scheme. The analysis is carried out for the Reynolds number and Hartman number. The ranges of the studied parameters are Reynolds number 300≤Re≤1000 and Hartmann number 0≤Ha≤10. The hemodynamic effects on the bifurcated channel and elastic walls are calculated using velocity, pressure, wall shear stresses (WSS), and loads at the walls. The study shows there is an increase in boundary load as the values of the Hartman number increase hence WSS increases. On the other hand, an increase in the Reynolds number increases the resistance forces hence velocity and WSS decrease. Also, numerical values of WSS for rigid and elastic walls are calculated. Studies showed that WSS decreases for the FSI case when compare to CFD (computational fluid dynamic) case.